Some new Hermite-Hadamard type inequalities for generalized harmonically convex functions involving local fractional integrals - Sun, Wenbing; Xu, Rui (AIMS mathematics, 2021)
In this paper, we establish a new integral identity involving local fractional integral on Yang's fractal sets. Using this integral identity, some new generalized Hermite-Hadamard type inequalities whose function is monotonically increasing and generalized harmonically convex are obtained. Finally, we construct some generalized special means to explain the applications of these inequalities.